Antidiabetic Activity of Extract Combination of Orthosiphon aristatus and Oryza sativa L. var glutinosa - Eris Septiana; Nurul Maulida Rizka; Yadi Yadi; Partomuan Simanjuntak (Borneo Journal of Pharmacy, 2021)
Traditionally and scientifically, research has shown that Orthosiphon aristatus and Oryza sativa L. var. glutinosa have antidiabetic activity. The combination of two medicinal plants can increase their biological activity. This study aimed to determine the antidiabetic activity of O. aristatus and O. sativa L. var. glutinosa on single and combined extracts. Phytochemical screening of the single extract was done qualitatively. The α-glucosidase inhibitory method was used as an antidiabetic activity. The results showed that every extract contained alkaloids, steroids/triterpenoids, flavonoids, tannins, quinones, and coumarins. A single extract of O. sativa L. var glutinosa, O. aristatus, and their combinations (1:1, 1:2, and 2:1) had an α-glucosidase enzyme inhibitory activity with an IC50 value of 67.82, 80.93, 73.81, 88.72, and 61.51 µg/ml, respectively. The combination shows that the ratio of 1:1 was nearly additive, 1:2 was slight to moderate antagonism, and 2:1 was moderate to slight synergism. The combination of 96% ethanol extract of O. sativa L. var. glutinosa and O. aristatus in a ratio of 2:1 was the most effective in increasing its inhibitory activity.